Health promotion project: Its role in developing medical students’ soft skills - Norwati, Daud (2018)
Background: The Malaysian Qualification Framework has decided to include soft skills as a component that needs to be assessed during an educational programme in higher institutions. There are five soft skills domains which are; 1. Social skills and responsibility, 2. Value, attitude and professionalism, 3. Communication, leadership and team skills, 4. Information management and lifelong learning skills and 5. Managerial and entrepreneurial skills. During family medicine posting in Universiti Sultan Zainal Abidin, Terengganu, students are expected to do a health promotion project (HPP) as group work in health clinic. The health promotion project was selected after discussion with the family physician based on its importance and relevance. The target group was patients attending the health clinic. There were about 8 students in a group and each had their role in the HPP. The objective is to assess students’ perception on the role of health promotion project activity in developing their soft skills. Method: At the end of the posting, anonymous online feedback was used to ask whether the HPP had improved the 5 domains of soft skills. The response was in the form of scale from 1 to 5, from ‘strongly disagree’ to ‘strongly agree’. Data was analysed for mean and standard deviation. Results: Half of year 4 students have done family medicine posting by December 2017. Response rate was 96% (28/29). The mean (SD) for domains 1,2,3,4 and 5 were 4.4 (0.74), 4.3 (0.71), 4.5 (0.69), 4.1 (0.71) and 4.4 (0.68) respectively. Conclusion: Students felt that the HPP was useful in developing their soft skills. HPP should be continued as one of the activities during family medicine posting.